Accuracy of hemodynamic parameters derived by GE E-PiCCO in comparison with PiCCO® in patients admitted to the intensive care unit - Katarzyna Putko; Johanna Erber; Franziska Wagner; Daniel Busch; Hannah Schuster; Roland M. Schmid; Tobias Lahmer; Sebastian Rasch (Scientific Reports, 2023)
Abstract To evaluate the agreement and accuracy of a novel advanced hemodynamic monitoring (AHM) device, the GE E-PiCCO module, with the well-established PiCCO® device in intensive care patients using pulse contour analysis (PCA) and transpulmonary thermodilution (TPTD). A total of 108 measurements were performed in 15 patients with AHM. Each of the 27 measurement sequences (one to four per patient) consisted of a femoral and a jugular indicator injection via central venous catheters (CVC) and measurement using both PiCCO (PiCCO® Jug and Fem) and GE E-PiCCO (GE E-PiCCO Jug and Fem) devices. For statistical analysis, Bland–Altman plots were used to compare the estimated values derived from both devices. The cardiac index measured via PCA (CIpc) and TPTD (CItd) was the only parameter that fulfilled all a priori-defined criteria based on bias and the limits of agreement (LoA) by the Bland–Altman method as well as the percentage error by Critchley and Critchley for all three comparison pairs (GE E-PiCCO Jug vs. PiCCO® Jug, GE E-PiCCO Fem vs. PiCCO® Fem, and GE E-PiCCO Fem vs. GE E-PiCCO Jug), while the GE E-PiCCO did not accurately estimate EVLWI, SVRI, SVV, and PPV values measured via the jugular and femoral CVC compared with values assessed by PiCCO®. Consequently, measurement discrepancy should be considered on evaluation and interpretation of the hemodynamic status of patients admitted to the ICU when using the GE E-PiCCO module instead of the PiCCO® device.